Association between greenhouse working exposure and bronchial asthma: A pilot, cross-sectional survey of 5, 420 greenhouse farmers from northeast China. Issue 4 (3rd April 2019) - Liu, Shuo; Wolters, Paul J.; Zhang, Yibing; Zhao, Mingjing; Liu, Dan; Wang, Lingling; Zhao, Guangdan; Mao, Shitao; Wu, Lijian; Zhao, Hongwen; Wang, Xiaoge
Abstract: Long-term exposure to greenhouse environments exposes greenhouse workers to inhalation of antigens that can cause respiratory diseases. This study was conducted to investigate the prevalence and potential risk factors for bronchial asthma among the Chinese greenhouse workers based on questionnaire and spirometry data. This was an observational cross-sectional study, performed via stratified-cluster-random sampling. It was conducted in Liaoning Province from the northeast of People's Republic of China, using a population-based sample of 5, 880 workers at 835 plastic film greenhouses. All subjects were interviewed using a standardized questionnaire and underwent pulmonary function tests. Multiple logistic regression analysis was conducted to assess associations between self-reported factors of greenhouse worker exposure and bronchial asthma and to identify potential risk factors for this disease. A total of 5, 420 questionnaires were completed. The overall prevalence of asthma in greenhouse workers was 19.2% (1040/5420). Multiple logistic regression analysis revealed that the use of multiple pesticides (odds ratio [OR] 1.24, 95% confidence interval [CI] 1.03–1.49), bad odors in the greenhouse (OR = 1.26, 95% CI = 1.07–1.49), and report of the onset of cough when entering the greenhouse (OR = 1.25, 95% CI = 1.09–1.44) were associated with the development of asthma. In contrast, a higher body mass index (BMI >18.5 kg/m 2, OR = 0.93, 95% CI = 0.90–0.95), planting flowers (OR = 0.92, 95% CI = 0.87–0.98), open sidewall to outside (natural ventilation) for at least 30 min per event (OR = 0.82, 95% CI = 0.69–0.96), living in greenhouse (OR = 0.85, 95% CI = 0.73–0.99), and experiencing cough before 14 years old (OR = 0.61, 95% CI = 0.43–0.84) were protective factors to the presentation of asthma among greenhouse workers. Our results suggest that asthma is a major public health problem among Chinese greenhouse workers and more attention should be devoted to preventive measures and management of this disease.